Marks & Spencer: the quest to master the new millennium - Wilson, David (Henry Stewart Talks, 2016)
The case study looks at the efforts of Marks & Spencer’s management to save the company in the face of stiff brand competition in the early 2000s. Professor Wilson posits that the future success of Marks & Spencer’s relies on a clear, innovative business strategy; an effective board; and the input of staff and regional management.